Overview of fruit cracking in sweet cherry (Prunus avium L.): causes, testing methods, mitigation strategies, and research perspectives - Xu, Jingcheng; Chen, Linghui; Dong, Jun; Jiang, Linfang; Hong, Li (Frontiers in Sustainable Food Systems, 2025)
Sweet cherry (Prunus avium L.) is one of the fruits that are widely acclaimed around the world. However, its fruits are prone to cracking from onset of color to full maturity, especially in cherry-producing regions where rain events are common near harvest. Cracked cherries have an unpleasant appearance, as well as susceptible to invasion by fungal pathogens, therefore dramatically depreciated, incurring considerable economic losses to growers, quite dampening their planting enthusiasm, subsequently restricting the advancement of sweet cherry industry. The incidence and severity of fruit cracking in sweet cherry are affected by genotypic, environmental, as well as agronomic factors. This review provides an overview of the causes, testing methods, and mitigation strategies related to fruit cracking in sweet cherry. Based on recent research advances, this review proposes the perspectives that developing crack resistant varieties is as a promising strategy to mitigate fruit cracking in sweet cherry.